The importance of indigenous knowledge and practices associated with rabies in Oyo State, Nigeria: implication for global health training at the University of Ibadan (2013)
Traditional African societies possess indigenous knowledge systems (IKS) which enable the indigenous people to comprehend ancestral-communal efforts that have been established to generate socio-economic, physical and mental wellbeing (alaafia). These knowledge systems not only reflect the people's health values and needs, they have developed in response to local environments and conditions. This paper argues that Africa's health systems including traditional veterinary practices, must be rooted in her indigenous knowledge for sustainability, studied and incorporated into formal health education curricula and research for greater understanding, and utilization to make her a relevant partner in the global health education. Using a combination of literature review, rapid key informant and in-depth interviews conducted in twelve purposively selected communities in six local government areas of Oyo state, this. paper presents the knowledge and practices of the indigenous people about rabies. Local farmers, hunters and' traditional healers who kept and used dogs claimed that rabid dogs and their human victims were curable and regularly cured with local herbs (apaasa, imi-esu, goat weed) and materials (adi-eyan). Orthodox veterinary practitioners stated that there was no cure for rabid dogs but human victims were often treated of the symptoms of rabies in human hospitals. The paper stresses the importance of indigenous veterinary knowledge and practices related to human-animal diseases control and advocates the need for their integration into the health education curricula of higher education and research in Africa to encourage knowledge-documentation and sharing and promote global health education for the benefits of the people.